Ensino do pensamento computacional por meio de histórias em quadrinho apresentando conceitos da robótica com sucata - Batista, Natália de Santana (2022)
Context: With the emergence of more and more technologies and professions, new adaptation needs arise, from the professional to the new employability challenges, being necessary to start such adaptation from childhood. Objective: Thus, this article aims to use Computational Thinking (CT) through Comics with concepts of Robotics with Scrap, since the CT brings a form of multidisciplinary problem solving that can adapt the way to acquire new knowledge, as well as the use of comics brings a way to acquire such knowledge. Method: To carry out this work, the Design Science Research (DSR) method was used, which consists of bringing a research approach based on the definition of two objectives, solving a practical problem in a specific context through an artifact and generating new scientific knowledge. Results: As a result, we have artifacts such as comics and guides, in addition to the positive evaluation by Education professionals who analyzed the artifacts with more than 90% approval and positive comments, with an increase in the difficulties faced. Conclusions: Coming to the conclusion that, besides bringing information, the artifacts can be used in the classroom by Education professionals for the teaching and development of CT in elementary school children.